Board social capital and excess CEO returns - Sauerwald, S.; Lin, Z.; Peng, Mike (John Wiley & Sons, 2016)
Excess CEO returns refer to CEO financial returns in excess of shareholder returns. How do boards rein in excess CEO returns? Introducing a social capital view of board monitoring, we suggest that boards face two competing normative pressures - corporate elite norms and monitoring norms. How boards conform to such normative pressures for controlling excess CEO returns is affected by their external and internal social capital. Further, we substantiate our arguments by showing that powerful CEOs and institutional investors may facilitate or constrain the normative pressures existing in the social network and alter the effects of board social capital on excess CEO returns. Data from a sample of U.S. corporations listed on the Standard and Poor's 1,500 index from 1999 to 2010 largely support our framework.